Exposure to titanium dioxide and risk of lung cancer in a population-based study from Montreal - Boffetta, Paolo; Gaborieau, Valerie; Nadon, Louise; Parent, Marie-Elise; Weiderpass, Elisabete; Siemiatycki, Jack (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study assessed the lung cancer risk from exposure to titanium dioxide, an important pigment with limited evidence of carcinogenicity in experimental animals but sparse data for humans. ' ' METHODS ': 'The risk of lung cancer among residents in Montreal, Canada, was analyzed, including 857 histologically confirmed cases of lung cancer diagnosed during 1979-1985 among men aged 35-70 years and a group of referents comprising 533 randomly selected, healthy residents and 533 persons with cancer in organs other than the lung. Exposure to titanium dioxide and other titanium compounds was assessed by a team of industrial hygienists on the basis of a detailed occupational questionnaire. ' ' RESULTS ': 'Thirty-three cases and 43 referents were classified as exposed to titanium dioxide. The odds ratio was 0.9 [95% confidence interval (95% CI) 0.5-1.5]. No trend was apparent according to the estimated frequency, level, or duration of exposure. The odds ratio was 1.0 (95% CI 0.3-2.7) for medium or high exposure for at least 5 years. Few subjects were classified as exposed to titanium dioxide fumes or to other titanium compounds, but the risk of lung cancer was nonsignificantly increased for exposure to these agents. ' ' CONCLUSIONS ': 'Although misclassification of exposure and low exposure prevalence might have resulted in false negative results, this study does not suggest that occupational exposure to titanium dioxide increases the risk of lung cancer.
Keywords: epidemiology; exposure; lung cancer; lung neoplasms; occupational exposure; population-based study; risk; titanium dioxide